Norma [opera in two acts (1831)] - Bellini, Vincenzo 1801-1835 (Opus Arte, 2008)
A layered, timeless drama in which Norma is the archetypal successful woman struggling to retain her dominant but vulnerable position
Live-Aufn. Het Muziektheater, Amsterdam, 2005. - Ital. gesungen, Untertitel engl., franz., dt., span., ital. , niederländ. - Interpr.: Hasmik Papian [Norma]. Hugh Smith [Pollione]. Irini Tsirakidis [Adalgisa]. Giorgio Giuseppini [Oroveso]. Anna Steiger [Clotilde]. Carlo Bosi [Flavio]. Chorus of De Nederlandse Opera. Netherlands Chamber Orchestra. Julian Reynolds, conductor. Guy Joosten, stage director. - Extra features: introduction, directed by Roeland Hazendonk, including interviews with principal members of the cast and the artistic team; illustrated synopsis; cast gallery
Keywords: Operas; Film; DVD-Video